Functions And Authority Of The Village Consultative Body (BPD) In Development Planning In Ampera Village, Pagimana District, Banggai Regency - Latuba, Mirawati; Nani, Yacob Noho; Pakaya, Rahmatia (Public Policy Journal, 2025)
This study examines the functions and authority of the BPD as legislators, facilitators, and dynamizers in development planning in Ampera Village. The research approach is descriptive and qualitative, employing data collection techniques such as observation, interviews, and documentation studies. The analysis was carried out through several main stages, namely data reduction, data presentation, and conclusion drawing. The informants for this study consisted of BPD members, the village head, and the hamlet head as representatives of the community. The study's results indicate that the Village Consultative Body's legislative function in Ampera Village is still in the planning stage and has yet to produce a valid village regulation, making it suboptimal. However, the Village Consultative Body in Ampera Village has effectively carried out its functions and authority as a facilitator by connecting the aspirations of the community and the village government through a forum for participatory village development planning, which encourages their involvement in the development planning process. The Village Consultative Body in Ampera Village has also effectively carried out its functions and authority as a dynamizer. They not only act as a conduit for aspirations but also as supervisors of development and mediators in problem-solving. This active role contributes to increasing community trust in the village government and creates a conducive atmosphere for development.